A new visual-guided and partition-based multi-setup 3D printing system. (April 2023) - Deng, Xiaoke; Li, Zhaoyu; Wang, Xiangyu; Shi, Fan; Tang, Kai
Abstract: Additive manufacturing, also known as 3D printing, has become a powerful and versatile means of manufacturing for almost any applications in our daily lives. A frequently encountered problem in printing, particular in consumer or lower-end applications, is how to print a workpiece whose dimensions exceed the working space of the printer at hand. Rather than opting for the costly solution of getting a new and larger printer (and hence more expensive and also other induced hassles), a more plausible solution would be an algorithmic one, which is the objective of this paper. We present a partition-based multi-setup printing process planning algorithm that, given the CAD model of an oversized workpiece, will be able to determine a continuous printing path with multiple workpiece setups to correctly print out the workpiece on the same printer. To answer the challenge of workpiece localization during the change of workpiece setups in the middle of printing, we propose a visual-guided workpiece localization system. Both computer simulation and physical printing experiments are carried out, and the results give a positive confirmation on the feasibility and effectiveness of the proposed multi-setup printing methodology and our enabling printing process planning algorithm. Highlights: A multi-setup strategy for printing a workpiece whose dimensions exceed the working space of the given printer is proposed. A visual-guided workpiece localization system which is independent of the workpiece geometry is developed. A partition-based multi-setup printing process planning algorithm is presented to determine a continuous multi-setup printing path for correctly printing the entire workpiece as a single unit. Simulations and experiments are conducted to verify the effectiveness of the proposed works.